ANALISIS PEMANFAATAN FASILITAS PANGKALAN PENDARATAN IKAN KASIWA KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Muhammad Ardiansyah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
This research was conducted from November 9, 2021, to December 09, 2021. This research aimed to determine the condition of the Kasiwa fish landing base facility, analyze the utilization of the Kasiwa landing base facility, Mamuju District, West Sulawesi province, as well as the development of the Kasiwa mamuju fish landing base facility. Data collection was carried out through a field survey. and interviews using a list of questions (questionnaires). Analysis of the data using the suitability analysis of the utilization of the Kasiwa mamuju fish landing base facility. The results of this study indicate that the utilization of the Kasiwa fish landing base facility in the Mamuju district is in good condition and it is necessary to develop the Kasiwa fish landing base facility to make it easier for fishermen to unload and handle the catch.